2016
DOI: 10.1002/pbc.25982
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perspective of Quality of Life of Retinoblastoma Survivors

Abstract: Health-related quality of life (HRQOL) in retinoblastoma survivors was assessed using parent proxy report of PedsQL(TM) 4.0 generic core scale. One hundred twenty-two parents of retinoblastoma survivors filled the questionnaire satisfactorily. This was compared with parent-reported HRQOL of 50 siblings. The median age of survivors was 98 (range, 60-247) months and male:female ratio was 2:1. The overall parent-reported HRQOL was significantly worse in survivors as compared to controls (74.4 ± 8.5 vs. 85.1 ± 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…Moreover, our results indicate that survivors of RB with monocular vision, who did not have motor deficits, also tended to have lower physical and social QOL compared with the typically developing children. These results are congruent with several previous studies showing that survivors of childhood RB have a lower QOL 25,26.…”
supporting
confidence: 93%
“…Moreover, our results indicate that survivors of RB with monocular vision, who did not have motor deficits, also tended to have lower physical and social QOL compared with the typically developing children. These results are congruent with several previous studies showing that survivors of childhood RB have a lower QOL 25,26.…”
supporting
confidence: 93%
“…In addition, patients not only have to withstand a delay in visuo-motor integration in comparison with their healthy peers (Ross et al, 2001), but also a life-long fear of developing recurrences, second primary malignancies, further loss of vision and passing on the disease to their offspring (van Dijk et al, 2010). When parents had to compare the quality of life of their affected children with healthy siblings, their report was significantly worse regarding the former (Batra et al, 2016a). A study comparing self (child)versus parental evaluation of health-related quality of life showed that parents reported worse on emotional domains (Batra et al, 2016b).…”
Section: Evaluation Of Quality Of Lifementioning
confidence: 99%
“…The current study investigated the feasibility of RetinoQuest in clinical practice. Earlier studies have shown that computer-assisted data collection on HRQoL data is feasible in daily clinical practice [ 4 , 5 , 12 17 , 19 , 22 , 29 ]. In line with the findings of de Bree et al [ 14 ], we showed that RetinoQuest is a feasible e-health application to monitor HRQoL in Rb survivors in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Other concerns relate to recurrence of the disease, passing Rb to offspring, second primary tumors, restrictions in education and professional career, mobility, self-care, and relationships [ 3 8 ]. Furthermore, the parents’ ability to cope with the stress associated with diagnosis, treatment, and heredity impacts the psychosocial functioning and development of their affected child [ 2 , 7 , 9 12 ].…”
Section: Introductionmentioning
confidence: 99%